Inoculation Methods to Determine Resistance of Phalaenopsis amabilis (L.) Regeneratded from Irradiated Protocorms to Dickeya dadantii - Putri, Halida Adistya; Sukma, Dewi; Sudarsono, Sudarsono; Purwito, Agus (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2024)
Soft-rot disease (SRD) in Phalaenopsis, caused Dickeya dadantii, has resulted in significant losses in the orchid sector in Indonesia. This study aimed to evaluate the inoculation method of Dickeya dadantii and identify the resistance response of individual regenerated plantlets of Phal. amabilis from irradiated protocorm. A detached leaf assay was used to evaluate the inoculation method and resistance response of SRD. Based on the results of this study, Dickeya dadantii bacteria could only infect the leaves through wounding tissue. The density of bacteria that could infect leaf tissue was OD600 = 0.2. All dilution factors tested caused soft rot symptoms in P. amabilis. On the other hand, Vanilla planifolia only showed symptoms at a dilution factor of 10-0. Four accessions of regenerated plantlets from irradiated protocorms were resistant to SRD. They were from irradiation 5 Gy (IP 05 Gy-23, IP 05 Gy-31, and IP 05 Gy-33) and one accession from the control treatment or without irradiation (IP 0 Gy -1). These results showed that 5 Gy irradiation increased plant resistance to SRD in Phalaenopsis. A dose of 5 Gy can potentially produce mutant lines resistant to SRD in Phalaenopsis or other plants, too.